23 1/2 lies : thrillers - Patterson, James, 1947-; Paetro, Maxine; Bourelle, Andrew; Estleman, Loren D. (Grand Central, 2023)
"Enjoy three heart-racing thrillers from the New York Times bestselling master of suspense. 23 1/2 LIES: Lindsay Boxer's estranged father is gunned down execution-style, and her investigation uncovers life-altering truths. FALLEN RANGER: To Rory Yates, being a Texas Ranger means absolute loyalty to the badge. But he's put through the ultimate test when an armored car robbery suspect might be an ex-Ranger gone rogue. WATCH YOUR BACK: When a starving artist is paid to expose his client's cheating wife, can he paint the picture that will save his own life?"--